KINERJA RANTAI PASOK PRODUK SAYURAN DI KOTA BOGOR - Himmatul Miftah; Arti Yusdiarti; Dean Riza Rivanda (Mimbar Agribisnis: Jurnal Pemikiran Masyarakat Ilmiah Berwawasan Agribisnis, 2019)
Increasing in population, vegetable consumption levels and healthy lifestyle offer a big opportunities for the vegetables marketing. These opportunities need to be utilized to bring benefit for vegetable farmers. Profits can be achieved through the selection of a supply chain that favors farmers through a development model of vegetable supply chain in Bogor City.The purpose of this research is to analyze the components of supply chain system by vegetable farmers to traditional markets in terms of their supply chain performance. The vegetables analyzed were spinach, potato, tomato, and onion. Data obtained by survey and observation. The main respondents are farmers vegetable producers who sell to traditional markets, either directly or through intermediaries. Three retailers as respondents were chosen purposively in each vegetable at Bogor and Jambu Dua market. Other respondents are marketers and farmers who were chosen by the retailers (snowball sampling method). Data were analyzed to determine the supply chain performance through SCOR method. The results showed that the producers spinach and tomato supplied from the farmers nearby to Bogor City. While other vegetables like onions and potatoes were supplied from farmers in West Java and mid Java. All vegetables studied in their distribution through equalization process. Performance of traditional vegetable supply chain has not yet integrated consumer expectation and producers/ farmers in planning, procurement, production, distribution, return, and action. This unoptimal performance of vegetable supply chain in traditional markets reviewed from supply chain reliability, responsiveness, flexibility, and assets management of supply chain.